2019
DOI: 10.1016/j.virusres.2017.11.020
|View full text |Cite
|
Sign up to set email alerts
|

A novel insect-infecting virga/nege-like virus group and its pervasive endogenization into insect genomes

Abstract: Insects are the host and vector of diverse viruses including those that infect vertebrates, plants, and fungi. Recent wide-scale transcriptomic analyses have uncovered the existence of a number of novel insect viruses belonging to an alphavirus-like superfamily (virgavirus/negevirus-related lineage). In this study, through an in silico search using publicly available insect transcriptomic data, we found numerous virus-like sequences related to insect virga/nege-like viruses. Phylogenetic analysis showed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(75 citation statements)
references
References 89 publications
1
74
0
Order By: Relevance
“…Previous studies have revealed the presence of EVEs related to plant-infecting viruses within arthropod genomes (14,35,36). Interestingly, many of these EVEs correspond to viral families known to contain viruses that are transmitted by insect vectors but that do not replicate within insects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have revealed the presence of EVEs related to plant-infecting viruses within arthropod genomes (14,35,36). Interestingly, many of these EVEs correspond to viral families known to contain viruses that are transmitted by insect vectors but that do not replicate within insects.…”
Section: Discussionmentioning
confidence: 99%
“…While we cannot draw conclusions regarding the origin of these EVEs related to plant viruses based on the present data, others have suggested that the phylogenetic position of such EVEs firmly within the known genetic diversity of plant viruses, as well as the fact that some plant virus-related EVEs encode putative proteins homologous to the movement proteins of plant viruses, indicates that they are derived from bona fide plant viruses rather than undocumented insect viruses (36). Yet others argue for the existence of ancient and undocumented viral families occupying phylogenetic gaps between insect-and plant-infecting viruses and that EVEs related to plant-infecting viruses may in fact be derived from novel families of insect-infecting viruses (35).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the presence of several nege/kita-like viruses and related virus-like sequences, has been reported from invertebrate meta-transcriptome analyses or surveys of insect transcriptomic datasets (Shi et al, 2016a;Kondo et al, 2019). To further explore the presence of unknown nege/kitavirus-like sequences, we conducted tBlastN searches against publicly available TSA datasets using BARV-1 and BARV-2 sequences as queries.…”
Section: Search For Nege/kita-like Virus Sequences Using the Tsa Datamentioning
confidence: 99%
“…Members of these two proposed genera, together with two proposed taxa of arthropod-restrictive viruses, "Nelorpivirus" and "Sandewavirus, " which all have non-segmented genomes, could be classified into a novel viral family or be assigned to the family Kitaviridae. However, it is to too early to establish a family for these viruses or to assign them into the Kitaviridae, because there is no reliable statistical support for these lineages within the currently available phylogenetic trees (Kallies et al, 2014;Nunes et al, 2017;Kondo et al, 2019;Ramos-González et al, 2020; Figure 3). The result of molecular phylogenetics indicate that the two major lineages of kitaviruses (cile/higreviruses and bulunerviruses) are not monophyletic, which all have two or multi-segmented RNA genomes and separately encode their replicase (RdRp) and SP24 family protein on the different segments (Locali-Fabris et al, 2006;Melzer et al, 2013;Hao et al, 2018), suggesting that genome segmentation possibly occurred independently during the evolution of kitaviruses.…”
Section: Phylogenetic Relationships Among Nege/kita-and Nege/kita-likmentioning
confidence: 99%
See 1 more Smart Citation